KENDALA DALAM PENATALAKSANAAN KEILITIS EKSFOLIATIF (Laporan Kasus) - Indriasti Indah Wardhany; Titiek Setyawati (Faculty of Dentistry, Universitas Indonesia, 2015)
Exfoliative cheilitis is a rare chronic superficial inflammation disorder which affect vermilion border of the lips, especially lower lip. This disorder mostly happens in woman. The characteristics of this disease are a large amount production and desquamation of the keratin layers. The etiology and pathogenesis of exfoliative cheilitis is unknown. Diagnosis of exfoliative cheilitis can only be established if the conditions od the disease couldn't be connected to others factors. Exfoliative cheilitis is very resistant to many treatment modalities, which gave a difficulty to determining a therapy with an optimum result. Topical steroid was the most effective therapy for the disease. Antifungal therapy can be used only if there is a secondarily infection caused by Candida . This case report is about an exfoliative cheilitis on 42 years-old women with unknown etiology backgrounds. On intra-oral examination we found out that there were several focus of infections that can delay the healing processes. The patient's conditions were resolved after a few month of topical steroid therapy, a month of antifungal therapy and management of the focus of infections. An exact diagnosis, an appropriate management, good corporation between sections which are related to patient condition and patient corporation are very important on the healing of exfoliative cheilitis.